AXIOLOGICAL FUNDAMENTS OF RELATIONS BETWEEN ETHICS AND POLITICS - Podrez, Ewa (Studia Philosophiae Christianae, 2020)
The subject of this article is the axiological basis of relations between morality and politics. The author shows anthropological and metaphysical origins of the idea of common good in social life. What role does morality play in political activity and where are moral foundations of a democratic state to be found? How to ensure the presence of moral values in public life (education, participation, common good, open society). The most important questions include: Who is responsible for ideas of democracy? Can democracy survive without a footing in pre–democratic values?